2019
DOI: 10.20473/jbe.v7i22019.94-102
|View full text |Cite
|
Sign up to set email alerts
|

The Antidiphtheria Antibodies of Seroepidemiology Survey Among Adolescents in Bangkalan and Kediri Districts

Abstract: Background: An increase in diphtheria cases has occurred in East Java Province since 2011. The resistance level to diphtheria is considered as the most important cause. Purpose: The study aims analyzed the immunity level immunity to diphtheria in adolescents aged 16-18 years old in Bangkalan and Kediri Districts. Methods: This study was a cross-sectional study, conducted on students in eleven grade of senior high schools (SMAN) from both districts. The inclusion criteria included being 16-18 years old and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
2
1
3
Order By: Relevance
“…Samples were not selected proportionally by district. It predicted influence the result which is different to the previous study, considering that prevalence of diphtheria in each district were different 17 , 19 . The data was not analyzed by immunization history and history of the exposure to the diphtheria cases because of data limitation.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Samples were not selected proportionally by district. It predicted influence the result which is different to the previous study, considering that prevalence of diphtheria in each district were different 17 , 19 . The data was not analyzed by immunization history and history of the exposure to the diphtheria cases because of data limitation.…”
Section: Discussioncontrasting
confidence: 82%
“…Samples were not selected proportionally by district. It predicted influence the result which is different to the previous study, considering that prevalence of diphtheria in each district were different 17,19 .…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Although an annual report revealed its high coverage, we predicted the real condition to be different. A previous study showed that the high seroprotective level of antibodies was induced by natural immunity rather than vaccination coverage (18,19). Furthermore, we detected no definite cause of its high distribution in females.…”
Section: Discussioncontrasting
confidence: 70%